2013
DOI: 10.1016/j.bbamcr.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

1,8-Cineol inhibits nuclear translocation of NF-κB p65 and NF-κB-dependent transcriptional activity

Abstract: Natural plant-derived products are commonly applied to treat a broad range of human diseases, including cancer as well as chronic and acute airway inflammation. In this regard, the monoterpene oxide 1,8-cineol, the active ingredient of the clinically approved drug Soledum®, is well-established for the therapy of airway diseases, such as chronic sinusitis and bronchitis, chronic obstructive pulmonary disease and bronchial asthma. Although clinical trials underline the beneficial effects of 1,8-cineol in treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 66 publications
5
59
0
Order By: Relevance
“…Overexpression of cytokines and chemokines induced by influenza virus infection is dependent on the NF-kB signaling pathway [47,48]. Previous study showed that 1,8-cineol can inhibit nuclear translocation of NF-kappaB p65 and NF-kappaBdependent transcriptional activity [20,22,49]. In present study, compared with the IFV-C group, the expression of NF-kB p65 (the major component of NF-kB) was significantly decreased in the lung after influenza virus challenge in cineol-treated mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overexpression of cytokines and chemokines induced by influenza virus infection is dependent on the NF-kB signaling pathway [47,48]. Previous study showed that 1,8-cineol can inhibit nuclear translocation of NF-kappaB p65 and NF-kappaBdependent transcriptional activity [20,22,49]. In present study, compared with the IFV-C group, the expression of NF-kB p65 (the major component of NF-kB) was significantly decreased in the lung after influenza virus challenge in cineol-treated mice.…”
Section: Discussionmentioning
confidence: 98%
“…1,8-cineol strongly inhibits tumor necrosis factor (TNF)-α and IL-1β level [12,21]. Likewise, 1,8-cineol is also known to inhibit directly signaling via NF-kB [22]. Previous studies have shown that proinflammatory cytokines are markedly elevated during influenza virus infection, and this Bcytokine storm^is hypothesized to be the main cause of mortality [23,24].…”
Section: Introductionmentioning
confidence: 98%
“…Eucalyptol interfered with arachidonic acid metabolism in blood monocytes of asthma patients, inhibited LPS‐induced IL‐1β production in human monocytes, suppressed LPS‐induced production of nitric oxide in a macrophage cell line and diminished LPS‐induced expression, translocation and transcriptional activities of early growth response factor 1 and NF‐κB in human cell lines (Juergens et al, ,b; Zhou et al, ; Kim et al, ). Finally, eucalyptol also has antioxidant and antimicrobial activity that may contribute to its anti‐inflammatory effects in some pathological conditions (Keinan et al, ; Hendry et al, ; Sadlon and Lamson, ; Greiner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Greiner et al have demonstrated that 1,8-cineol inhibits the nuclear import of the transcriptional activator protein NF-κB p65 and correspondingly its transcriptional activity (18) leading to decreased cell proliferation. Our findings of the suppressive influence of 1,8-cineol on relevant components in the WNT pathway-driven cancer progression, such as GSK-3 (Ser 9/21), β-catenin, and WNT11, describe a completely novel mode of action, which may lead to novel treatment approaches of this natural drug.…”
Section: Discussionmentioning
confidence: 99%
“…Various biological activities have been attributed to 1,8-cineol, which is commonly applied to treat various chronic and acute inflammatory airway diseases as well as patients with polyposis nasi. Recently, it has been shown that 1,8-cineol leads to decreased activity of the pro-inflammatory NF-κB-signaling by inhibiting its nuclear translocation (17, 18). …”
Section: Introductionmentioning
confidence: 99%